2010
DOI: 10.1902/jop.2010.100113
|View full text |Cite
|
Sign up to set email alerts
|

Single Flap Approach With and Without Guided Tissue Regeneration and a Hydroxyapatite Biomaterial in the Management of Intraosseous Periodontal Defects

Abstract: SFA with and without HA/GTR seems to be a valuable minimally invasive approach in the treatment of deep intraosseous periodontal defects. Under the present experimental conditions, the additional HA/GTR protocol offers no significant adjunctive effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
149
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(164 citation statements)
references
References 39 publications
7
149
0
8
Order By: Relevance
“…Recent studies also showed retardant effects of HAp nanoparticles on cancer cells [8]. Currently, HAp is commonly the material of choice for various biomedical applications, e.g., as a replacement of bony and periodontal defects [9], alveolar ridge [10], middle ear implants [11], tissue engineering systems [12], drug delivery agent [13], and bioactive coating onto metallic osseous implants [14]. The general importance of HAp and its derivatives has also led to its numerous other non-medical industrial and technological applications [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies also showed retardant effects of HAp nanoparticles on cancer cells [8]. Currently, HAp is commonly the material of choice for various biomedical applications, e.g., as a replacement of bony and periodontal defects [9], alveolar ridge [10], middle ear implants [11], tissue engineering systems [12], drug delivery agent [13], and bioactive coating onto metallic osseous implants [14]. The general importance of HAp and its derivatives has also led to its numerous other non-medical industrial and technological applications [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The application of these new surgical approaches alone and with bone substitute materials and barrier membranes or enamel matrix derivates (EMD) showed that there are no significant advantages of the adjunctive use of these materials [8,9,10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, if the target site is the interproximal area, it would be more severe than in the buccal or lingual surface because the interdental papilla and connective tissue in the col area are devoid of adequate blood supply and healing capacity. To overcome these problems, several approaches (minimally invasive surgical technique, 6 SPPF, 11 single flap approach 14 etc.) have been introduced.…”
Section: Discussionmentioning
confidence: 99%